Análisis de percepción de la integración de sistemas de gestión (2018)
This article aims to publicize the perception of the integration of management systems of different types of actors that have participated or have training in integration, specifically the scope is developed on the following standards: NTC-ISO 9001, OHSAS 18001 and NTC-ISO 14001, these can be implemented individually or integrated within an organization, which affects whether to obtain the different types of benefits, opportunities and efforts by an entity. For this, the main components of an Integrated Management System - IMS were identified, based on the development of a theoretical framework of representative authors in the subject, with which a valid instrument was constructed that allows, through its completion, to rescue the valuation and positive or negative appreciation regarding the different elements that are associated with the implementation of an IMS. The results have been beneficial to understand how the application of each element is estimated and its tendency in the opinion of the different participants in an established space and time of transition of ISO standards. The instrument designed gives the opportunity and possibility to be used to verify how the acceptance of concepts, methodologies, sequence of integration and components evolves and determine strategic aspects, benefits, difficulties and possible disadvantages that may be caused when implementing an IMS in an organization. The importance of this work is to take a first step to identify the perception of the integration of management systems, in a transition stage of the NTC-ISO 9001 standard to be able to assess to what extent there is homogeneity or heterogeneity in the appreciation of the elements what make it up.